Modelling, identification and structural damage investigation of the Neoria monument in Chania - Barbara Charalambidi; Panagiotis Koutsianitis; Siphesihle Mpho Motsa; Georgios Tairidis; Amalia Kasampali; Georgios Drosopoulos; Maria Stavroulaki; Georgios Stavroulakis (Developments in the Built Environment, 2022)
The structural behavior of Neoria masonry monument is studied here. The determination of structural and material properties of a partially collapsed monument and the evaluation of existing damages and their importance for further restoration studies are not trivial tasks. The investigation has been based on detailed geometric data, collected from sources and in-situ measurements. For the mechanical analysis, finite element models have been created with different level of detail, including simplified description of documented damages. Modal analysis is assisted by micro-tremor measurements. Comparison of the predictions with the experimentally measured quantities, allows the determination of material parameters with higher accuracy. A least square technique assisted by the modal assurance criterion has been used, by driving the model from a Python script. A comparison of collapse predictions based on modified pushover analysis, with classical modal analysis has been performed. An explanation of existing damages is attempted, based on the numerical models.